2015
DOI: 10.1016/j.cma.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Real time parameter identification and solution reconstruction from experimental data using the Proper Generalized Decomposition

Abstract: Some industrial processes are modelled by parametric partial differential equations. Integrating computational modelling and data assimilation into the control process requires obtaining a solution of the numerical model at the characteristic frequency of the process (realtime). This paper introduces a computational strategy allowing to efficiently exploit measurements of those industrial processes, providing the solution of the model at the required frequency. This is particularly interesting in the framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…When the just described separated representation constructor is used in nonsymmetric problems, the obtained solution contains more modes than those provided by the Singular Value Decomposition (SVD) (or its multidimensional counterpart, the High Order Singular Value Decomposition (HOSVD)) applied to the problem solution computed by using standard discretization techniques. Thus, the decomposition provided by the PGD constructor is not optimal [27]. This reveals that some modes do not make an important contribution to the solution reconstruction and are not necessary in the reduced basis.…”
Section: Pgd Formulationmentioning
confidence: 91%
“…When the just described separated representation constructor is used in nonsymmetric problems, the obtained solution contains more modes than those provided by the Singular Value Decomposition (SVD) (or its multidimensional counterpart, the High Order Singular Value Decomposition (HOSVD)) applied to the problem solution computed by using standard discretization techniques. Thus, the decomposition provided by the PGD constructor is not optimal [27]. This reveals that some modes do not make an important contribution to the solution reconstruction and are not necessary in the reduced basis.…”
Section: Pgd Formulationmentioning
confidence: 91%
“…An upgrade of this technique is the proper generalized decomposition (Nadal et al, 2015), suitable to be used in any engineering and biomedical engineering problem. Another approach is the spectral representation method which similarly expands the random field as a sum of trigonometric functions with random phase angles and amplitudes (Eiermann et al, 2007; Stefanou, 2009).…”
Section: Uncertainty and Variability In Computational Models: Propagamentioning
confidence: 99%
“…To avoid redundant measurements, the authors [25] suggested an approach without using the exclusion disk strategy. However, the approach therein only allows one sensor per mode.…”
Section: Remarkmentioning
confidence: 99%
“…We remark that there are many other ways to accommodate noise into models and predict the state space from reconstruction-for example, Kalman filtering [21], empirical interpolation method [22,23], and proper generalized decomposition [24,25]. The purpose of our paper is to understand the effect of noisy and bad measurements within the POD framework.…”
Section: Introductionmentioning
confidence: 99%